Nova generacija digitalnih prijenosnih sustava - Mikula, Miroslav; Jelušić, Frane (Promet - Traffic&Transportation, 2012)
Digitalization of telecommunications systems is currently in progress. In the light of the fact that the transmission systems make one of the fundamental parts of the system, their capacities are important. This year a new generation of digital transmission systems with up to this point of time the highest rate of 2,5 Hb it/sec has been introduces. The paper discusses the features and possibilities of new systems and their integration into the strategy of telecommunications system digitalization.